A Perfect Marriage: Child-related Pensions and Public Education - Michael Voigtländer (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2004)
In the present paper the effects of different pay-as-you-go pension systems on fertility decisions of a representative household are examined. Thereby, the analysis focuses especially on the interplay of parental quantity and quality decisions, introduced by Becker (1960). As it will be shown, a traditional pay-as-you-go system in either case distorts decisions of parents leading to an erosion of the financial basis of the system. In contrast, the assessment of a child-related pay-as-you-go system is ambiguous. If parents are solely responsible for expenditures on the quality of children, it is inefficient, too. However, if it is combined with a device like public education, optimality can be restored.
Keywords: D10; H55; I20; 330; Pay-as-you-go; child-related pension; quantity and quality of children; Gesetzliche Rentenversicherung; Umlageverfahren; Familienleistungsausgleich; Bildungsinvestition; Bildungspolitik; Theorie